PEMBELAJARAN MENCATAT TEKS PROSEDUR MENGGUNAKAN METODE DEMONTRASI - Rizal Seafulloh; Muhammad Ginanjar; Enung Nurhayati (IKIP Siliwangi, 2019)
The purpose of this study is an effort to increase the skills of recording junior high school students in the text material of the procedure using the demonstration method. Writing is an aspect used by people for relationships or conveying indirect messages. the method of observation used by researchers is the experimental method, with the design of a pre-test one post-test group. The research sample was VIII SMP students. The data collection tool used is the learning implementation plan, observation sheet and test sheet. The results of the initial verification and final verification show an improvement in students' writing skills in the text material. Procedures use the demonstration method. The results of the study can be concluded that there is an increase in students' writing skills in the text material of the procedure using the demonstration method. The results of teacher learning observations in the 85% class were carried out and student learning in the 80% class was conducted. The results of this study indicate an increase in students' writing skills in the text material. Procedures use the demonstration method and can improve well according to the objectives expected in this study.